1974
DOI: 10.1021/ma60037a011
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Regular Enantiomeric Sequences

Abstract: Cylindrical coordinates and symmetries of regular enantiomeric sequences were derived on the basis of eigenvalue-eigenvectors solns. to the Eyring-transformation matrix, and were used to show that the general structure of conformationally equiv. enantiomers was a ring. Helical structures could be formed in the case of quasi-conformational equivalence between the monomeric units. For regular L,D copolypeptides, these helical structures were stabilized by both van der Waals and H bond interactions, and were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
169
0
18

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(193 citation statements)
references
References 0 publications
6
169
0
18
Order By: Relevance
“…As can be seen, the hd u-u i values predicted for a/cyc[(QALA) 2 ] in DMF and chloroform solutions are identical (4.76 AE 0.10Å) and practically matched the distance observed by Fourier-transform infrared spectroscopy, electron diffraction and X-ray crystallographic analyses (4.73Å). 68 supporting the theory that this conformation is intrinsically favored for the octapeptide. Fig.…”
Section: View Article Onlinesupporting
confidence: 67%
“…As can be seen, the hd u-u i values predicted for a/cyc[(QALA) 2 ] in DMF and chloroform solutions are identical (4.76 AE 0.10Å) and practically matched the distance observed by Fourier-transform infrared spectroscopy, electron diffraction and X-ray crystallographic analyses (4.73Å). 68 supporting the theory that this conformation is intrinsically favored for the octapeptide. Fig.…”
Section: View Article Onlinesupporting
confidence: 67%
“…Theoretical investigations (De Santis, Morosetti & Rizzo, 1974) have shown that such a singular feature, since the conformational equivalence is assumed, results in the stabilization of cyclic structures with S n point symmetry (n = 6, 8, 10 ...) characterized by an ion complexing cavity, or, when the strict equivalence is slightly relaxed, in fiat helical structures with innerchannel dimensions suitable for the ion passage. Both channels and carriers are generally characterized by an arrangement of the polar groups in the inner regions whereas the side chains point to the outer regions of the molecule.…”
mentioning
confidence: 99%
“…Ten years ago we predicted (De Santis, Morosetti & Rizzo, 1974) the carrier behaviour of cyclo-(L,D-hexaproline) as well as the channel activity of the homologous polyproline with alternating L and D configurations.…”
mentioning
confidence: 99%
“…The alternating chirality of the amino acids in the macrocycle leads to amide bonds that alternate in orientation perpendicular to the plane of the CP rings 16 . As a result, a contiguous intermolecular hydrogen-bonded network arises, resulting in the formation of nanotubular structures.…”
mentioning
confidence: 99%